Morphological and phenological shoot plasticity in a Mediterranean evergreen oak facing long-term increased drought. - Limousin, Jean-Marc; Rambal, Serge; OURCIVAL, JEAN-MARC; Rodriguez-Calcerrada, Jesus; Pérez-Ramos, Ignacio M; Rodríguez-Cortina, Raquel; Misson, Laurent; Joffre, Richard (Oecologia, 2012)
Mediterranean trees must adjust their canopy leaf area to the unpredictable timing and severity of summer drought. The impact of increased drought on the canopy dynamics of the evergreen Quercus ilex was studied by measuring shoot growth, leaf production, litterfall, leafing phenology and leaf demography in a mature forest stand submitted to partial throughfall exclusion for 7 years. The leaf area index rapidly declined in the throughfall-exclusion plot and was 19% lower than in the control plot after 7 years of treatment. Consequently, leaf litterfall was significantly lower in the dry treatment. Such a decline in leaf area occurred through a change in branch allometry with a decreased number of ramifications produced and a reduction of the leaf area supported per unit sapwood area of the shoot (LA/SA). The leafing phenology was slightly delayed and the median leaf life span was slightly longer in the dry treatment. The canopy dynamics in both treatments were driven by water availability with a 1-year lag: leaf shedding and production were reduced following dry years; in contrast, leaf turnover was increased following wet years. The drought-induced decrease in leaf area, resulting from both plasticity in shoot development and slower leaf turnover, appeared to be a hydraulic adjustment to limit canopy transpiration and maintain leaf-specific hydraulic conductivity under drier conditions.
Keywords: allometry; Dehydration; Droughts; France; leaf area; leaf demography; litterfall; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: physiology; Plant Shoots; Plant Shoots: growth & development; Quercus; Quercus: physiology; shoot growth; Trees

Morphological and phenological shoot plasticity in a Mediterranean evergreen oak facing long-term increased drought. - Limousin, Jean-Marc; Rambal, Serge; OURCIVAL, JEAN-MARC; Rodriguez-Calcerrada, Jesus; Pérez-Ramos, Ignacio M.; Rodríguez-Cortina, Raquel; Misson, Laurent; Joffre, Richard (Oecologia, 2012)
Mediterranean trees must adjust their canopy leaf area to the unpredictable timing and severity of summer drought. The impact of increased drought on the canopy dynamics of the evergreen Quercus ilex was studied by measuring shoot growth, leaf production, litterfall, leafing phenology and leaf demography in a mature forest stand submitted to partial throughfall exclusion for 7 years. The leaf area index rapidly declined in the throughfall-exclusion plot and was 19% lower than in the control plot after 7 years of treatment. Consequently, leaf litterfall was significantly lower in the dry treatment. Such a decline in leaf area occurred through a change in branch allometry with a decreased number of ramifications produced and a reduction of the leaf area supported per unit sapwood area of the shoot (LA/SA). The leafing phenology was slightly delayed and the median leaf life span was slightly longer in the dry treatment. The canopy dynamics in both treatments were driven by water availability with a 1-year lag: leaf shedding and production were reduced following dry years; in contrast, leaf turnover was increased following wet years. The drought-induced decrease in leaf area, resulting from both plasticity in shoot development and slower leaf turnover, appeared to be a hydraulic adjustment to limit canopy transpiration and maintain leaf-specific hydraulic conductivity under drier conditions.
The following values have no corresponding Zotero field: accession-num: 22159896
Keywords: allometry; Dehydration; Droughts; France; leaf area; leaf demography; litterfall; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: physiology; Plant Shoots; Plant Shoots: growth & development; Quercus; Quercus: physiology; shoot growth; Trees